Generation of proton-and alpha-induced nuclear cross-section data via random forest algorithm: Production of radionuclide111in - Hamid, M.A.B. (MDPI AG, 2021)
We investigated the generation of proton-and alpha-induced nuclear cross-section data in the production of Indium-111 (111 In) for application in nuclear medicine. Here, we are interested in three reaction channels, which are109Ag (Î±, 2n),111Cd (p, n) and112Cd (p, 2n), in the production of111 In. A random forest algorithm was used to generate nuclear cross-section data by using an experimental nuclear cross-section from the Experimental Nuclear Reaction Data (EXFOR) database as input. Hence, reasonably accurate regression curves of nuclear cross-section data could be produced with the evaluated nuclear data library ENDF/B-VII.0 set as the benchmark. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.